Jumping performance among competing elite male handball - Setuain, I. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Handball, is one of the most challenging sports for the knee joint. Although female handball players are one of the most exposed athletes to the ACL injury, the incidence of this injury on their male counterparts is not infrequent. Persisting strength and neuromuscular control deficits may be observed among the athletes who had suffered ACL injury, despite having complete the rehabilitation process due to inadequate or incomplete rehabilitation. This factor could be one of the explaining reasons for the ACL reinjury rates among this population. Measuring jumping performance variables such as stance phase contact time, flight time and mechanical power output during the rehabilitation process would help to minimize high-cost reinjury rate among handball elite athletes. PURPOSE: To describe jumping performance among a group of 13 male handball elite athletes using a previously validated jump test battery. Secondly, to identify possible differences between injured and uninjured extremities, in vertical and horizontal jump flight times, stance phase contact time, mechanical power, and reached distance obtained. We hypothesized that previously injured extremities would show deficits in jumping performance despite the injured athletes have completed their rehabilitation process and being competing at the maximum level. METHODS: 13 male elite athletes (6 previously injured and reconstructed and 7 uninjured control subjects) were evaluated performing a previously validated jump test battery that includes bilateral drop jump, unilateral drop jump, unilateral countermovement jump, unilateral triple jump for distance and the cross over hop for distance. Height (m), flight time (s), stance phase contact time (s), mechanical power (W•kg-1) and distance (m) were obtained in each jump test performed. For the unilateral jump tests, comparison was made between reconstructed legs and the dominant ones of the uninjured subjects. For the bilateral drop jump test, comparison was made between reconstructed and uninjured subjects. RESULTS: Previously ACL reconstructed athletes demonstrated significantly lower mechanical power values during the unilateral drop jump (11,06 vs. 17,43 W•kg-1; P<0.05) on their reconstructed leg compared with the healthy legs of the uninjured subjects. No significant differences were observed in the other variables recorded. CONCLUSION: Previously ACL reconstructed athletes may cope with some functional deficits once returning to competition, such as in lower mechanical power output ability in the injury limb, potentially increasing their reinjury risk. Restoration of these deficits would help to decrease the reinjury rates among this population.